2021
DOI: 10.1186/s13071-021-05045-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of malaria co-infection among individuals with visceral leishmaniasis in Africa and Asia: a systematic review and meta-analysis

Abstract: Background Malaria and visceral leishmaniasis (VL) co-infection can occur due to the overlapping geographical distributions of these diseases; however, only limited data of this co-infection have been reported and reviewed. This study aimed to explore the pooled prevalence and characteristics of this co-infection using a systematic review approach. Methods The PubMed, Web of Science and Scopus databases were searched for relevant studies. The quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Furthermore, co-infections by several parasites are not uncommon. For example, those by Schistosoma haematobium and Plasmodium falciparum are frequent [ 96 , 97 , 98 , 99 ]. It has been shown that children with S. haematobium and P. falciparum coinfections exhibit lower expression levels of LILRB2, one of the receptors of HLA-G in B cells and neutrophils.…”
Section: Hla-g Expression In Parasitic Diseasesmentioning
confidence: 99%
“…Furthermore, co-infections by several parasites are not uncommon. For example, those by Schistosoma haematobium and Plasmodium falciparum are frequent [ 96 , 97 , 98 , 99 ]. It has been shown that children with S. haematobium and P. falciparum coinfections exhibit lower expression levels of LILRB2, one of the receptors of HLA-G in B cells and neutrophils.…”
Section: Hla-g Expression In Parasitic Diseasesmentioning
confidence: 99%
“…Nevertheless, CRP was better than PCT at discriminating viral infections from bacterial infections [ 17 ]. PCT was more beneficial for critical care in the hospital context as it reacted faster to infections [ 10 , 35 , 36 ]. As PCT is also more rapidly eliminated, sharply decreasing PCT after treatment might be a marker for judging the curative effect of malaria as suggested by previous studies [ 36 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The misidentification of P. ovale as P. vivax or P. knowlesi as P. malariae is frequent and leads to underreported P. ovale and P. knowlesi cases [ 7 , 8 ]. In addition, other tropical diseases are reported in patients with malaria as a co-infection, making the clinical diagnosis difficult [ 9 , 10 , 11 , 12 , 13 , 14 ]. Moreover, the decision for the treatment of malaria relies on clinical assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in 2014 in northwest Ethiopia, on the border with Sudan, showed that 4.2% of VL patients were co-infected with Plasmodium ( 13 ). Overall, a meta-analysis study with data from 1991 to 2020 suggests that the prevalence of Plasmodium co-infection among individuals with VL ranges from 7 to 18% in Africa and Asia, according to the endemicity of VL and malaria in the evaluated area ( 18 ).…”
Section: Plasmodium Spp and Leishmania Sp...mentioning
confidence: 99%